Primary Care Providers' Use of Genetic Services in the Southeast United States: Barriers, Facilitators, and Strategies - Erin Seibel; Gwen Gunn; Nadia Ali; Ellen Jordan; Aileen Kenneson (SAGE Publishing, 2022)
Introduction/Objectives: Collectively, genetic diseases are not that rare, and with increasing availability of genetics-informed healthcare management, primary care providers (PCPs) are more often asked to screen for or provide genetic services. Previous studies have identified barriers that impact PCPs' ability to provide genetic services, including limited knowledge, training, and time/resources. This study set out to identify specific barriers limiting genetics service provision by PCPs within the Southeastern Regional Genetics Network (SERN) and resources that would help eliminate those barriers. Methods: PCPs were recruited through provider networks and invited to participate in semi-structured interviews, conducted via Zoom, recorded, and transcribed verbatim. Interview transcripts were independently coded by 2 coders using MAXQDA software. Thematic analysis was conducted. Results: Eleven interviews were conducted. Three predominant themes emerged from the data regarding factors impacting use of genetic services: system-wide factors, provider-specific factors, and patient factors. System-wide barriers included a lack of genetics providers and logistic challenges, which led to some PCPs coordinating referrals with other specialists or independently managing patients. Regarding provider-specific barriers, PCPs reported lack of genetics knowledge making referrals challenging. When possible, many PCPs contacted genetics providers for assistance. When not possible, some PCPs reached out to other colleagues or specialists for guidance. Patient-specific barriers included concerns or lack of information regarding genetics and unmet social needs. Many PCPs provided additional education regarding genetics appointments or testing benefits to their patients. Assistance from genetic counselors, electronic medical record systems that support referral to genetics, prior experience referring to genetics, established communication channels with genetics professionals, and highly motivated patients all facilitated improved collaboration with genetic services. PCPs provided suggestions for future resources to support interactions with genetics, including clear referral guidelines, increased access to genetics providers, improved test ordering processes, increased access to genetic education, and communication systems. Conclusions: PCPs face barriers at 3 different levels when engaging with genetic services: systems, providers, and patients. This study identified strategies that PCPs use to address these barriers, which are dependent on individual resources and practice settings. These strategies demonstrate resourcefulness in working to incorporate genetics into clinics operating at maximum capacity. By targeting barriers that uniquely impact providers, systems, and patients, as well as building upon strategies that PCPs are already using, medical providers can support PCPs to help with the provision of genetic services.